Peningkatan Ketahanan Aus pada Baja Tahan Karat Martensitik 13Cr AISI 410 setelah Proses Austenisasi dan Tempering [Improvement of Wear Resistance of 13Cr AISI 410 Martensitic Stainless Steel after Austenitizing and Tempering Process] - Apriani, Annisa Siti; Anwar, Moch. Syaiful; Rusnaldy; Mabruri, Efendi (Jurnal Metalurgi, 2017)
The turbine blades that were developed from martensitic stainless steel 13Cr are usually operate on high rotation speed in steam power plants and often found to be failures in the material. One of the failure causes is the presence of foreign material that gives the abrasion impact on the surface of the turbine blade. The aim of this study is observed the effect of austenitization and tempering temperatures on the hardness and abrasion resistance of 13Cr martensitic stainless steel. The examinations were carried out i.e. hardness Rockwell C and abrasion resistance. The optimum hardness values obtained on 13Cr martensitic stainless steel which austenitizing at 1050 °C and tempering of 600 °C. The increasing of tempering temperature in the 13Cr stainless steel does not give a linear negative effect on the abrasion resistance of the steel.